La reescritura en Eliseo Diego: entre el olvido y la memoria (Crítica) - Mussó Mujica, Luis Carlos (2014)
The author of this article aims to discover, in the poetry of Eliseo Diego, the role and importance of the rewriting game as an element of memory and as a fluctuating lyrical “I”, distributed in facets and fractured spaces, typical of a neo-Baroque ethos. He also follows the poetics that are applied to the poems of the Cuban author, in the sense of expression of consciousness of a crisis imbued with melancholy given the transience of things and time. The author warns that his starting point is that the works maintain a tendency towards doubt and the unique concept; going beyond the conventions between the poem and reader’s expectations.